Isolation and determination of chemical compounds from red algae, Gracilaria manilaensis gracilaria sp. and G. changii and their bioactivities - Desy Fitrya, Syamsumir
Five species from Gracilariaceae, one Ulvaceae and one Scytosiphonaceae, two polysaccharides from Gracilaria spp. and three cholesterol derivatives were screened for their cytotoxicity (MTT assay method), antioxidant (DPPH free radical scavenging assay, xanthine oxidase inhibitory assay and total phenolic content assay), antibacterial (disc diffusion method) and acetylcholinesterase inhibitory assay (TLC bioautographic method). Three species of Gracilariaceae were selected for further isolation due to the high quantity sample available and preliminary screening of biological activites on crude extracts. Three compounds were successfully isolated in this study, namely cholest-5-en-3-ol isolated from Gracilaria manilaensis, Gracilaria sp. and G. changii; hexadecanoic acid from G. manilaensis and G. changii\ and 1-(4'methoxyphenyl)-3-(2",4",6"-trihydroxyphenyl-3-hydroxypropanone from Gracilaria sp. The structures of these compounds were determined based on spectral data analysis and comparison with literature review.